60.2: Invited Paper: Advanced In‐cell Touch Technology for Large Sized Liquid Crystal Displays. Issue 1 (June 2015) - Kim, Cheolse; Lee, Deuk Su; Kim, Ju Han; Kim, Hun Bae; Shin, Seung Rok; Jung, Ji Hyun; Song, In Hyuk; Jang, Chul Sang; Kwon, Keuk Sang; Kim, Sung Ho; Kim, Geon Tae; Yoon, Jeong Hwan; et al.
Abstract : We propose an advanced in‐cell touch (AIT) sensor integrated on TFT substrate. The proposed touch sensor perceives selfcapacitance formed between touching object and sensing electrode which is made by common electrode of AH‐IPS panel. This new touch sensor shows above 50dB‐signal‐to‐noise ratio and multi‐touch function without loss of transmittance. Finally we have succeeded in in‐cell touch panel development of 15.6" FHD for notebook PC and 7" WVGA for automotive which supports 2mm‐thick glove touch.